A Longitudinal 1H-MRS Study of the Anterior Cingulate Gyrus in Child and Adolescent Victims of Multiple Forms of Violence. (March 2018) - Milani, Ana Carolina Coelho; Foerster, Bernd; Cogo-Moreira, Hugo; Farias, Thiago Michel de Brito; Salido, Francisco; Carrete, Henrique; Mello, Marcelo Feijo; Jackowski, Andrea Parolin
Background: The anterior cingulate gyrus is involved in the extinction of conditioned fear responses and is implicated in the pathophysiology of posttraumatic stress disorder. The expression of N-acetylaspartate and choline may be altered in the anterior cingulate gyri of children and adolescents with posttraumatic stress disorder. Methods: We conducted a proton magnetic resonance spectroscopy study, longitudinally investigating N-acetylaspartate/creatine and choline/creatine ratios in the anterior cingulate gyri of children and adolescents, aged from 8 to 12 years, who had been exposed to various forms of violence or were non-trauma control. Based on baseline posttraumatic stress symptoms ("sub-clinical"), participants were divided into two groups: posttraumatic stress (n = 19) and control (n = 19). Proton magnetic resonance spectroscopy scans were repeated a year later in trauma exposed participants. Trauma assessments included the Childhood Trauma Questionnaire. Results: Exploratory analyses revealed a significant negative correlation between follow-up anterior cingulate gyrus N-acetylaspartate/creatine and Childhood Trauma Questionnaire scores in posttraumatic stress (r = −0.62, p = 0.01) but not control group (r = 0.16, p = 0.66). However, we found no significant differences in anterior cingulate gyrus N-acetylaspartate/creatine or choline/creatine between posttraumatic stress and control. In addition, there were no significant effects of time, group, or time-by-group interactions. Conclusions: In this pediatric population, anterior cingulate gyrus N-acetylaspartate/creatine and choline/creatine were not affected by posttraumatic stress and on average these metabolites remained stable over time. However, the study provided intriguing preliminary evidence revealing that participants suffering from posttraumatic stress at baseline have shown, a year later, reduced anterior cingulate gyrus N-acetylaspartate/creatine among those with high trauma severity. This pilot evidence warrants replication in future studies to confirm these findings and to determine the longitudinal effects and interactions between childhood posttraumatic stress and trauma.